Oxidative Stress as "Mother" of Many Human Diseases at Strong Clinical Impact - Federico Cacciapuoti (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2016)
Likewise the 1991 Gulf War, known as a "mother of all battles", oxidative stress (OS) can be considered as a "mother" of many human diseases life threatening. OS is a condition in which oxidation exceeds the anti-oxidant reactions, causing an imbalance between oxidative and anti-oxidant systems, with prevalence of reactive oxygen species ROS [1-5]. These include: peroxide, superoxide, hydroxyl radical, singlet oxygen and others. Under normal conditions ROS are maintained at physiological levels by several endogenous antioxidant systems, as superoxide dismutase, catalase, glutathione peroxidases, lacto-peptidases, glutathione reductase and others [6]. However, if active ROS are excessively generated, the balance between the formation and the removal of these species is lost. Generating oxidative damage (disruption between antioxidant defenses and ROS production) [7]. ROS can be generated from both endogenous and exogenous sources. Endogenous ROS are produced in normal metabolic reactions. Exogenous ROS derive by exposure to cigarette smoke, environmental pollutants, consumption of alcohol in excess, exposure to ionizing radiations, viral and bacterial infections, and others [8]. Individual, hereditary factors, and lifestyle are the main determinants of OS.